Determination of Nitrate Pollution Levels on an Argic Phaeozem in Order to Apply Fertilizers - Moldovan, Lavinia; Mărghitaș, Marilena; Poruțiu, Andra (Proenvironment, 2016)
Unlike other essential plant nutrition elements, soil nitrogen does not come from rocks or minerals from the earth'sÂ crust, its appearance and accumulation is subject to a number of biological processes. The nitrogen content of the soil is closely related to the soil organic matter content, in the composition of which nitrogen enters at a rate of about 5%. Lately,Â for assessing the level of available nitrogen in the soil, it becomes more widely spread the method of determining theÂ nitrification ability that is based on biological nitrogen mineralization in soil under controlled incubation. In Romania,Â nitrate poisoning is still a problematic reality, especially in the northeastern region of the country. Elevated nitrates /nitrites in soil composition caused 84 cases of acute poisoning in Romania, and even deaths, just four years ago. SoilÂ nitrates come from atmospheric nitrogen fixation by many plant species (vegetables) and are present even in the absenceÂ of nitrogen fertilization, the latter being but another major source of nitrates. Nitrates in groundwater come from theÂ rainwater washing of nitrates that naturally exist in the soil surface (thus reaching the water table), or they can haveÂ fertilizer as a source. The natural nitrate concentration in groundwater is normally less than 10 mg/l. In most communes and villages in Romania, water from the wells is polluted with substances from animal waste, manure stored directly onÂ the ground and not waterproofed latrines in private households. Soil nutrient pollution has negative consequences onÂ crops and the environment. Excess nutrients weaken crop plants, making them more vulnerable to diseases and pests. ThisÂ excess reduces plant resistance to drought, heat and cold, and production decreases. The last 30-40 years signal in a varietyÂ of situations, the generalization growth of N-NO3-concentrations in soil, water and plant products and the phenomenonÂ of excess nitrates is especially linked to the activities in agriculture and to uncontrolled organic and mineral fertilizingÂ technologies [4].